PENGARUH PENDIDIKAN KEWIRAUSAHAAN, EFIKASI DIRI, DAN POLA PIKIR KEWIRAUSAHAAN TERHADAP INTENSI BERWIRAUSAHA MAHASISWA FAKULTAS EKONOMIKA DAN BISNIS UNESA - Prawesti, Marisa Intan; Cahya, Septyan Budy (Jurnal Pendidikan Tata Niaga (JPTN), 2024)
This study aims to analyze the effect of entrepreneurship education, self-efficacy, and entrepreneurial mindset on entrepreneurial intention of students at the Faculty of Economics and Business, Surabaya State University. The method used in this research is data analysis technique with Structural Equation Modeling Partial Least Squares (SEM-PLS) using SmartPLS 3 software, by distributing questionnaires to the sample of this study, namely students who have taken entrepreneurship courses in 2020, 2021, and 2022. The results of this study are that among the variables studied, self-efficacy and entrepreneurial mindset have an influence on the entrepreneurial intention of FEB Unesa students, while in this study the entrepreneurship education variable has no effect on entrepreneurial intention. Future researchers are advised to explore other factors that may affect entrepreneurial intentions outside of this study, so that it can help broaden insights into the factors that play a role in student entrepreneurial intentions.